Comprensión de datos de medición inteligente para optimización del sistema de comunicación inalámbrica - Orbe Guato, Christian Renato (2015)
This paper presents a proposal to show the relationship between a smart metering with mass communication media. The first one is the measurement system of the electric power, through a database, which represents the residential electrical consumption, this content has a big amount of data and its advantage is to transmit by means of the wireless communication without any drawbacks, the technique applied to this system is the use of a mathematical tool, that displays some special features of how to perform analysis in time and frequency, plus translations and dilations parent function from among others. When handling a large amount of information certain drawbacks such as sending all the data for a given environment is presented, there are also problems of storage and collection of such information. This tool is known like Wavelet and it allows to compress information into big volumes since its structure gives a selection of parameters, which would be taken into consideration in the structure, and those that are below the threshold and those that are not mentioned in the parameters, will be set to zero. There is a requirement for this, and it is to convert the compressed signal to a signal that maintains its authenticity and not to differ from the original signal. The resulting value of the compression is a wave that will be affected in translation and scale, later must decompress the signal, so that information back to their original data